IMPLEMENTASI PROGRAM BANTUAN PANGAN NON-TUNAI (BPNT) MELALUI E-WARONG DI DESA SUKAMAJU KECAMATAN CIKAKAK KABUPATEN SUKABUMI - Herdiawan Waryadi; Nanon Hanriana (STISIP Widyapuri Mandiri, 2022)
This research is motivated by the suspicion that the implementation of the Non-Cash Food Assistance (BPNT) program through e-warong in Sukamaju Village, Cikakak District, Sukabumi Regency has not been optimal in meeting the food needs of the community. The purpose of this research is to determine: (1) employee behavior (2) work relations between employees, (3) employee communication, and (4) the leadership of the Village Head in relation to the implementation of the Non-Cash Food Assistance (BPNT) program to fulfill the needs food in Sukamaju Village, Cikakak District. This study uses a qualitative approach. The informants of this research were the Head of Sukamaju Village, PKH BPNT Facilitator in Sukamaju Village, and KPM BPNT Sukamaju Village. The results of the study include (1) employee behavior in relation to the implementation of the Non-Cash Food Assistance (BPNT) program to fulfill food needs in Sukamaju Village, Cikakak Subdistrict, is quite good, (2) working relations between employees in relation to the implementation of the Non-Cash Food Assistance (BPNT) program. ) to fulfill food needs in Sukamaju Village, Cikakak Subdistrict, (3) employee communication in relation to the implementation of the Non-Cash Food Assistance (BPNT) program to meet food needs in Sukamaju Village, Cikakak Subdistrict, is quite good, and (4) the leadership of the Village Head in relation to the implementation of the Non-Cash Food Assistance (BPNT) program to meet food needs in Sukamaju Village, Cikakak District is quite good. Keywords: Implementation, program, BPNT, e-Warong Abstrak Penelitian ini dilatarbelakangi adanya dugaan bahwa implementasi program Bantuan Pangan Non Tunai (BPNT) melalui e-warong Di Desa Sukamaju Kecamatan Cikakak Kabupaten Sukabumi belum optimal dalam memenuhi kebutuhan pangan masyarakat. Adapun tujuan dari penelitian ini adalah untuk mengetahui: (1) perilaku pegawai (2) hubungan kerja antar pegawai, (3) komunikasi pegawai, dan (4) kepemimpinan Kepala Desa dalam kaitan dengan implementasi program Bantuan Pangan Non Tunai (BPNT) untuk pemenuhan kebutuhan pangan di Desa Sukamaju Kecamatan Cikakak. Penelitian ini menggunakan pendekatan kualitatif. Informan penelitian ini adalah Kepala Desa Sukamaju, Pendamping PKH BPNT Desa Sukamaju, dan KPM BPNT Desa Sukamaju. Hasil penelitian antara lain (1) perilaku pegawai kaitan dengan implementasi program Bantuan Pangan Non Tunai (BPNT) untuk pemenuhan kebutuhan pangan di Desa Sukamaju Kecamatan Cikakak cukup baik, (2) hubungan kerja antar pegawai dalam kaitan dengan implementasi program Bantuan Pangan Non Tunai (BPNT) untuk pemenuhan kebutuhan pangan di Desa Sukamaju Kecamatan Cikakak cukup baik, (3) komunikasi pegawai dalam kaitan dengan implementasi program Bantuan Pangan Non Tunai (BPNT) untuk pemenuhan kebutuhan pangan di Desa Sukamaju Kecamatan Cikakak cukup baik, dan (4) kepemimpinan Kepala Desa dalam kaitan dengan implementasi program Bantuan Pangan Non Tunai (BPNT) untuk pemenuhan kebutuhan pangan di Desa Sukamaju Kecamatan Cikakak cukup baik. Kata kunci: Implementasi, program, BPNT, e-Warong